Correlation analysis of the Th17/Treg ratio, LCDC-2, IP-10 and liver function in patients with AIH: Th17/Treg ratio, LCDC-2, IP-10 and liver function in patients with AIH - Zhang, Wei; Luo, Anqing; Wei, Yanfang; Su, Xue; Li, Zhengdeng; Yao, Huimei; Tian, Xin; Zheng, Sheng (Journal of Medical Biochemistry, 2026)
Objective To analyze the relationships between the ratios of helper T-cell 17/regulatory T-cell (Th17/Treg), serum Leukocyte Cell-Derived Chemotaxin 2 (LCDC-2), and Interferon γ-induced protein 10 kDa (IP-10) and liver function and posttreatment response in patients with autoimmune hepatitis (AIH).Methods For the case group, 204 AIH patients who were admitted to our hospital between January 2022 and January 2024 were chosen. The control group consisted of an additional 200 healthy people who were examined throughout the same time period. The Th17/Treg ratios, serum LCDC-2 and IP-10 levels, Indicators of liver function were examined between the case and control groups. Pearson correlation analysis was used to analyze the correlations between the Th17/Treg ratios in peripheral blood, serum LCDC-2 levels, IP-10 levels and liver function indicators. Additionally, based on their responses following treatment, all patients were split into two groups: 50 patients had poor responses and 154 patients had good responses. Using multivariate logistic regression, the risk factors for a poor reaction were examined.Results The Th17/Treg ratio and the serum LCDC-2, IP-10, aspartate aminotransferase (AST), and the case group's alanine aminotransferase (ALT) levels were greater than the control group's (P
Keywords: Autoimmune hepatitis; The ratio of helper T cells 17 to regulatory T cells; Immune response; Leukocyte Cell-Derived Chemotaxin 2; Interferon γ-induced protein 10 kDa